Entrepreneurial imagining: How a small team of arts entrepreneurs created the world's largest traveling carillon. Issue 2 (February 2022) - Elias, Sara R. S. T. A.; Chiles, Todd H.; Crawford, Brett
Although imagination has been recognized as essential to entrepreneuring, the processes by which entrepreneurs imagine and generate novelty remain insufficiently understood. To begin addressing this oversight, we propose a rhizomatic process model of entrepreneurial imagining that comprises five elements: experiencing, early creating, reaching an impasse and gestating, (re)creating and evaluating imagined futures, and choosing and enterprising . To generate this dynamic process model, we undertook an abductive, 25-month case study, guided by enactive research, to investigate how a small team of arts entrepreneurs created the world's largest traveling carillon. Our primary contribution is to offer new theoretical insights into entrepreneurial imagining as a complex, situated, relational performance that unfolds through conscious and unconscious, self-reflective and embodied processes.